2019
DOI: 10.1002/cpt.1645
|View full text |Cite
|
Sign up to set email alerts
|

Changing Body Weight–Based Dosing to a Flat Dose for Avelumab in Metastatic Merkel Cell and Advanced Urothelial Carcinoma

Abstract: Avelumab, an anti–programmed death‐ligand 1 monoclonal antibody approved for the treatment of metastatic Merkel cell carcinoma and platinum‐treated urothelial carcinoma, was initially approved with a 10 mg/kg weight‐based dose. We report pharmacokinetic (PK)/pharmacodynamic analyses for avelumab comparing weight‐based dosing and a flat 800 mg dose, developed using data from 1,827 patients enrolled in 3 clinical trials (NCT01772004, NCT01943461, and NCT02155647). PK metrics were simulated for weight‐based and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 28 publications
(76 reference statements)
1
53
0
Order By: Relevance
“…Although some difference in exposure to the drug was seen in the extremes of weight, overall there was considerable overlap seen in exposure for all weight quartiles. Similarly, the probabilities of AEs and responses were comparable across all weight quartiles 73 Durvalumab phase I study used doses ranging from 0.1 to 10 mg/kg every 2 weeks and 15 mg/kg every 3 weeks, and no DLTs were observed even with the highest dose 69 .…”
Section: Programmed Death and Programmed Death Ligand Axismentioning
confidence: 77%
“…Although some difference in exposure to the drug was seen in the extremes of weight, overall there was considerable overlap seen in exposure for all weight quartiles. Similarly, the probabilities of AEs and responses were comparable across all weight quartiles 73 Durvalumab phase I study used doses ranging from 0.1 to 10 mg/kg every 2 weeks and 15 mg/kg every 3 weeks, and no DLTs were observed even with the highest dose 69 .…”
Section: Programmed Death and Programmed Death Ligand Axismentioning
confidence: 77%
“…Subsequent indications of urothelial carcinoma (9 May 2017) and RCC (14 May 2017) followed, each with the recommended dose of 10 mg/kg q2wk. Novakovic et al demonstrated comparable exposure between 10 mg/kg q2wk and flat 800 mg q2wk, 64 which was the basis of the most recent Bavencio label change.…”
Section: Potential Opportunities For Cost Savingsmentioning
confidence: 96%
“…First, they revealed that BW contributes only marginally to inter-individual variability (IIV) of PK parameters, particularly the CL. Secondly, they made it possible to simulate flat dosing and then to compare simulated plasma ICI concentrations to actual concentrations corresponding to a mg/kg dose [ 21 , 39 , 42 , 43 ]. Flat dosing was not associated with a larger IIV in plasma concentrations, and led to statistically similar exposures, regardless of the dosing.…”
Section: Flat Dose and Modified Schedulesmentioning
confidence: 99%